1995
DOI: 10.1021/ie00044a013
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Polynuclear Aromatic Hydrocarbons in Water. 2. UV Radiation and Ozonation in the Presence of UV Radiation

Abstract: Direct photolysis with W radiation (254 nm) and oxidation with ozone combined with W radiation of three polynuclear aromatic hydrocarbons, fluorene, phenanthrene, and acenaphthene, has been studied. Quantum yields of the direct photolysis of the PAHs determined were 7.5 x mol(photon)-l for fluorene, phenanthrene, and acenaphthene, respectively. Contributions of direct ozonation, direct photolysis, and radical oxidation have also been estimated for the oxidation with ozone combined with W radiation. Fluorene is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(95 citation statements)
references
References 19 publications
2
90
3
Order By: Relevance
“…Gregory et al [30] reported no significant concentration effect on the quantum yield of dibenzothiophene sulfoxide over a range of 0.5-30 mM. In contrast Miller and Olejik [7] and Beltran et al [6] reported higher rates of photodegradation at higher initial concentration of FLU, chrysene, benzo[a]pyrne, phenanthrene, and acenaphthene. These results were explained by higher absorption by the organic compound as their concentration was increased and consequently the observed rate of the reaction increased.…”
Section: Initial Concentration Of Pahsmentioning
confidence: 97%
See 1 more Smart Citation
“…Gregory et al [30] reported no significant concentration effect on the quantum yield of dibenzothiophene sulfoxide over a range of 0.5-30 mM. In contrast Miller and Olejik [7] and Beltran et al [6] reported higher rates of photodegradation at higher initial concentration of FLU, chrysene, benzo[a]pyrne, phenanthrene, and acenaphthene. These results were explained by higher absorption by the organic compound as their concentration was increased and consequently the observed rate of the reaction increased.…”
Section: Initial Concentration Of Pahsmentioning
confidence: 97%
“…Among the engineered processes bioremediation is generally considered having cost and technical advantages [5]. Advanced oxidation processes (AOPs), by which hydroxyl radicals are generated in order to destroy the organic contaminant, were also studied as an alternative to or in combination with biodegradation for removal of PAHs from aqueous solutions [6][7][8][9][10]. The highly reactive hydroxyl radicals, generated during AOPs, can lead to complete mineralization of the pollutant but most typically lead to formation of products of higher polarity and solubility in water such as phenols, quinones, and acids [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the inactive biological forms, such as pyrene, acquire toxic properties under such conditions [Smol et al, 2011]. Ozone constitutes a more efficient and a safer oxidant, ensuring greater degree of PAH removal with much shorter contact time [Beltran, 1995]. However, the products of PAH oxidation with ozone may be toxic and rapidly react with chlorine; therefore, an additional process, e.g.…”
Section: Removal Of Hardly Bio-degradabale Organic Compounds From Wasmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) were also the subject of the study [9][10][11], but despite the importance of such investigation the literature is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of FLU, phenanthrene, and acenaphthene applying O 3 /UV was studied by Beltran et al [11]. The influence, among others, of the presence of hydroxyl radicals inhibitors and pH of the reaction solution was investigated.…”
Section: Introductionmentioning
confidence: 99%